Introducing the Meaning of Batik through Game and Appearance in Virtual Reality - Ag. Dicky Prastomo; Bayu Widiantoro (Graduate School of Institut Seni Indonesia Yogyakarta, 2018)
Batik is not just visually but also philosophically enticing. a brief history in 1755, in the era of “Keraton Surakarta” and “Keraton yogyakarta”, each kingdom has developed their own style including motif and coloring. Making a Batik is not just simply decorating, it is also form a repository of beliefs and values. youth or young one, need to examine and understand Batik with spesific meet their ways. A digital native generations. Visual communication research design offers a case study and visual etnography or visual decoding to describe, to compare, and to evaluate the pattern, beliefs and values. Overall, analysis of findings would clearly indicate that most of the target audiences are not interested to know what the meaning of Batik meaning, but they relay on smartphone gaming as daily activity. the like to know things through 2 dimesional game.